AN ANALYSIS OF IMPERATIVE SENTENCE ON MEDICINE PRODUCT - Aditya, Silvia Erlin; Andayani, Nike (JURNAL LITERARY CRITICISM, 2015)
Imperative sentence is sentence that used to express command, request, direction, and prohibition. Imperative sentence often be seen on many media, one of them is guidance for using on medicine product. Guidance for using medicine product is a horde of sentence that used to give guidance to the consumer in order to decrease the misuse of the medicine product. The existence of the guidance to use of medicine product is being the source of this analysis is supposed to bring us the classification of guidance of medicine product those are divided by several kinds of them, imperative as a command, request, direction, and also imperative sentence that used to give prohibition. The process of classifying of this analysis is helped by the descriptive qualitative method in order to make the analysis to be sharp enough and easy to get the aim of this analysis that will peel off the purpose of imperative sentence on medicine product by classifying on what type they are mostly formed consisted. After having analysis over the entire related source in the imperative sentence, the researcher found that there is a tendency at almost of the sources is included to imperative sentence as a direction with totally amount 20 cases, 15 cases are included to imperative sentence as direction, then 4 cases of imperative sentence as prohibition, the last is 1 case of imperative sentence as command. As said by Swan that the meaning of direction is guidance or guideline, the instruction to do something, Imperative sentence as direction is used to give some guidance to someone else to do or to use some product in right way. Keywords: Imperative Sentence, Medicine Product, Imperative Sentence as Direction